Analisis Pemanfaatan Aplikasi Website Museum Subkoss Garuda Sriwijaya Bagi Siswa SMA Negeri 5 Lubuklinggau - Agus Susilo; Nugroho Ponco Riyanto (Diakronika, 2023)
The background of this research problem is that currently students of SMA Negeri 5 Luibuklinggau do not know much about the Garuda Sriwijaya Subkoss Museum. In fact, if there is a website at the Garuda Sriwijaya Subkoss Museum, Lubuklinggau 5 State High School students can explore history skills digitally. In the formulation of the research problem, namely how to use the Garuda Sriwijaya Subkoss Museum website for learning History at SMA Negeri 5 Lubuklinggau. while the purpose of this study was to analyze the utilization of the Garuda Sriwijaya Subkoss Museum website as a support for the History learning system at SMA Negeri 5 Lubuklinggau. This research method is a descriptive qualitative research method. This qualitative research method is used with the support of several references obtained from books and relevant research journals. Reference sources that support this research are in the form of book sources obtained from the library of the PGRI Silampari University, the Garuda Sriwijaya Subkoss Museum, private collections and scientific journals relevant to research. The results of this study are the development of the Garuda Sriwijaya Subkoss Museum website and the utilization of the Garuda Sriwijaya Subkoss Museum website for history lessons at SMA Negeri 5 Lubuklinggau. The existence of a website application developed by the Garuda Sriwijaya Subkoss Museum is very useful for learning History. The use of the Garuda Sriwijaya Subkoss Museum website can provide understanding and knowledge for SMA Negeri 5 Lubuklinggau students in learning History. The conclusion of this study is the utilization of the Garuda Sriwijaya Subkoss Museum website media for learning History at SMA Negeri 5 Lubuklinggau. History teachers can combine website media with creative and innovative learning strategies and models.